Effect of Renewable Energy and Electric Vehicles on Smart Grid - A. Zaky, Alaa (Recent Innovations in Mechatronics, 2015)
Global electricity demands are increasing at rapid pace. Energy supply, their usage and technologies involved need to be more economical, environment friendly and socially sustainable. Efforts are being done all over the globe to reduce this green house effect; and renewable energy technologies to combat climate changes, which require extensive changes to the current electricity generation and distribution systems. To meet this goal, it is required to optimize the grid operations and available resources to meet the ever increasing energy demands in an efficient, effective and environment sustainable way. So strong and huge interests on smart grid have increased extensively in recent years around the world. This scenario could be a promising reason for future research in this area. This next form of electricity grid will be able to manage various parts of power production from power plants to the customers. Renewable energy sources appear strongly in smart grid so in this paper the effect of this sources will be studied also electric vehicles have a great effect on smart grid infrastructure ,communication and control this paper will discuss this effect if it come from the electric vehicle mode or vehicle to grid mode.